Perspectivas democráticas y crisis de desarrollo - Sunkel, Osvaldo (Estudios Internacionales, 1990)
The democratization process that has been developing in the last decade in Latin America presents important differences between countries. These refer, among others, to questions of intensity and depth, of periodicity and sequence in time, and of historical antecedents in institutional matters, socio-economic structure and political organization. It is possible to discern two sets of generalized trends, corresponding to two deep and long-term processes, unfortunately contradictory and colliding. On the one hand, a demand for democratization and citizen participation; On the other, a major and long-lasting development crisis. Both processes are embodied in social carriers, which make them express themselves as social conflict.